Up from empire: Booker T. Washington, Tuskegee, and Pan-Africanism in the age of U.S. and European imperialism - Smith, Kenneth (Kansas State University, 2024)
Since Washington’s “Atlanta Compromise” speech, as it was critically called by W.E.B. Du Bois, Booker T. Washington has become a controversial figure in Black history. While critics of Washington, including Du Bois, chided him as an accommodationist acquiescing to white societal demands, including imperial powers that viewed Washington’s speech as justification for subordination of colonial peoples, a deeper look at Washington’s vision of the Hampton-Tuskegee model shows how Washington viewed technical education as a solution to elevating the status of Black peoples by building diasporic connections. While these relationships were forged within the context of empire-building, they were not simply the product of imperialist designs. Instead, they were created largely by the agency of Black people themselves. Booker T. Washington and Tuskegee were vested in helping Black peoples in the pursuit of education, full citizenship, and economic independence, all crucial markers of freedom. Washington hoped that the Hampton-Tuskegee model would help create a cadre of future Black leaders. Since US imperialism coincided with European imperialism in the late nineteenth/early twentieth centuries, rather than waging a counteroffensive to imperialism, many Afro-Diasporic subjects sought to take advantage of the opportunities created by the emerging imperial structure. These initiatives illustrate the complex interplay between diasporization, or the process by which diasporas are made, how racial solidarity is perceived and what the barriers are to achieving it, and different forms of empire-building in this period. This work will examine how by working within imperialism’s discourse, Booker T. Washington, Tuskegee’s teachers, and its supporters used the Hampton-Tuskegee model to uplift Africans, African Americans, Afro-Puerto Rico, and Afro-Cubans and how it shaped larger diasporic connections. Lastly, this paper will look at how the Hampton-Tuskegee model continued and evolved after Washington’ death in 1915.
Keywords: Black History; African American; Africa; Latin America; Imperialism; Education